Qualitative and quantitative parameters analyses of buffalo ovaries (Research in Agriculture Livestock and Fisheries, 2024)
Buffalo ovaries were collected from abattoirs in Dhaka city. During collection, left and right ovaries were identified and recorded. After processing, the ovaries were categorized as (i) ovaries without corpus luteum (CL) and (ii) ovaries with corpus luteum (CL). Ovaries were then evaluated based on length (cm), width (cm), weight (g), total number of follicles on the surface of each category of ovaries, number of follicles aspirated, and total number of cumulus-oocyte-complexes (COCs). The experiment's findings indicated variations in the parameters related to the left and right ovarian categories. The CL% (27.12±0.11%) found highest in the right compared to the left (3.24±0.11%). The length (cm), width (cm), and weight (g) (2.75±0.06, 2.17±0.05, 4.74±0.13) were found significantly (p